Optimal high b‐value for diffusion weighted MRI in diagnosing high risk prostate cancers in the peripheral zone. Issue 1 (7th July 2016) - Agarwal, Harsh K.; Mertan, Francesca V.; Sankineni, Sandeep; Bernardo, Marcelino; Senegas, Julien; Keupp, Jochen; Daar, Dagane; Merino, Maria; Wood, Bradford J.; Pinto, Peter A.; Choyke, Peter L.; Turkbey, Baris
Abstract : Purpose: To retrospectively determine the optimal b‐value(s) of diffusion‐weighted imaging (DWI) associated with intermediate–high risk cancer in the peripheral zone (PZ) of the prostate. Materials and Methods: Forty‐two consecutive patients underwent multi b‐value (16 evenly spaced b‐values between 0 and 2000 s/mm 2 ) DWI along with multi‐parametric MRI (MP‐MRI) of the prostate at 3 Tesla followed by trans‐rectal ultrasound/MRI fusion guided targeted biopsy of suspicious lesions detected at MP‐MRI. Computed DWI images up to a simulated b‐value of 4000 s/mm 2 were also obtained using a pair of b‐values (b = 133 and 400 or 667 or 933 s/mm 2 ) from the multi b‐value DWI. The contrast ratio of average intensity of the targeted lesions and the background PZ was determined. Receiver operator characteristic curves and the area under the curve (AUCs) were obtained for separating patients eligible for active surveillance with low risk prostate cancers from intermediate–high risk prostate cancers as per the cancer of the prostate risk assessment (CAPRA) scoring system. Results: The AUC first increased then decreased with the increase in b‐values reaching maximum at b = 1600 s/mm 2 (0.74) with no statistically significant different AUC of DWI with b‐values 1067–2000 s/mm 2 . The AUC of computed DWI increased then decreased with the increase in b‐values reaching a maximum of 0.75 around b = 2000 s/mm 2 . There was no statistically significant difference between the AUC of optimal acquired DWI and either of optimal computed DWI. Conclusion: The optimal b‐value for acquired DWI in differentiating intermediate–high from low risk prostate cancers in the PZ is b = 1600 s/mm 2 . The computed DWI has similar performance as that of acquired DWI with the optimal performance around b = 2000 s/mm 2 . Level of Evidence: 4 J. Magn. Reson. Imaging 2017;45:125–131.